Effect of Seed Coating and PEG-Induced Drought on the Germination Capacity of Five Clover Crops - Kintl, Antonín; Huňady, Igor; Vymyslický, Tomáš; Ondrisková, Vladěna; Hammerschmiedt, Tereza; Brtnický, Martin; Elbl, Jakub (Plants (Basel, Switzerland), 2021)
The effect of coating the seed of clover crops by water absorbing seed process (WASP) technology pelletization on its germination capacity was studied in conditions of diverse drought intensities simulated by different concentrations of polyethylenglycol (PEG) 8000 solution. Drought resistance was monitored in the seed of five fodder clover species: Anthyllis vulneraria L., Medicago lupulina L., Trifolium repens L., Melilotus albus Medik. and Onobrychis viciifolia Scop. In the seed of given plant species, germination capacity was determined along with the share of dead and hard seeds. Although the coating significantly (p < 0.05) affected the drought resistance of seeds, the germination capacity increased only in conditions of milder drought (simulation with PEG: 0.1-0.3 mol). With the increasing intensity of drought induced by higher PEG concentrations (0.4-0.7 mol) the number of germinable seeds demonstrably decreased and the number of dead seeds increased in the coated seed as compared with the uncoated seed. The coated seed can be appropriate for use in M. lupulina, M. albus and T. repens, while the uncoated seed can be used in A. vulneraria and O. viciifolia.
Keywords: polyethylenglycol; hardseededness; seeds improvement; dead seeds; legumes; drought tolerance